Neutron heating assessment in Minerve reactor by using alanine/ESR dosimetry. (July 2020) - Rouihem, F.; Dridi, W.; Daoudi, M.; Blaise, P.; Geslot, B.; Farah, K.; Mustapha, B.; Hosni, F.
Highlights: Integrated dose at CEA Minerve reactor core was measured using alanine dosimeters. The neutron dose was specifically calculated by the use of neutron kerma factors. Neutron dose was compared to the experimental one to validate the dose measurement. Neutron dose represents the main dose in alanine at the core. The relative efficiency to 60 Co of neutron radiation was evaluated. Abstract: In the framework of the ICERR (International Center based on Research Reactors) project, the effect of neutron/gamma irradiation on material and dosimeters has been studied. In this work, we explore the alanine dose–response in the core of the MINERVE research reactor at the CEA Cadarache and we investigate the neutron heating effects in order to evaluate alanine neutron sensitivity. The measured dose of the alanine detector in the mixed gamma-neutron field was estimated by electron spin resonance spectrometry (ESR) with reference to an absorbed dose in water from a 60 Co gamma-ray beam. The experimental sources of uncertainties were reduced by using the optimum conditions of charged-particle equilibrium (CPE), obtained by introducing alanine dosimeters into the aluminum pillbox. Cavity correction factors and dose components were evaluated by the Monte Carlo code MCNP. The calculation showed an underestimated neutron dose with a (C/E) value of about 0.993 ± 10.83 % ( k = 1 ) . Results indicate that the fast neutron dose, mainly due to elastic neutron scattering on hydrogen nuclei, represents about 70 % of the total dose, while the gamma dose was found to be around 45 % of the neutron dose. Additionally, the neutron relative efficiency ( R E n ) to 60 Co gamma-radiation was estimated to be 0.544 ± 8 % k = 1 .